Konsep Pemilikan di dalam Islam - Abdullah, Nawi (Jurnal Usuluddin, 2004)
This article discusses the concept of ownership in Islamic perspective. It also attempts to check on various types of ownership and the limit to each type of ownership. In the Islamic Economic System, there are resources and goods, which can be owned individually, in-group and also those that has to be government owned to preserve the interest and welfare of the public. The concept of freedom and limitation on the ownership of resources and goods in the Islamic Economic System is to preserve the harmony and welfare of society in line with the syariah requirements.